Pencegahan Anemia Remaja Putri Melalui GEENZI (Gerakan Edukasi, Skrining dan Intervensi Gizi) - Shinta Lutfiani; Ana Zully Astuti; Alfina Damayanti; Bela Catur Sakti Rahayu; Eka Sularsih; Risma Aliviani Putri (Universitas Ngudi Waluyo, 2025)
Adolescent girls are a group that is vulnerable to anemia due to rapid growth and unbalanced nutrient intake. Anemia that is left untreated can have a negative impact on reproductive health and reduce the quality of future generations. Low knowledge about nutrition and lack of consumption of Blood Addition Tablets (TTD) also worsen the condition and adolescents aged 12-17 years who experience mild anemia as many as 9 people have Hb <11 gr/dl. The implementation method used in this community service is health counseling given to 4 targets, namely pregnant women, postpartum mothers, toddlers and adolescents. However, the priority problem in RT 5 of Gedangank Village, namely the lack of knowledge about anemia in adolescents. This community service was carried out in Gedanganak Village, East Ungaran District, Semarang Regency, on adolescent girls aged 13-17 years totaling 20 people, on June 14, 2025. The results of community service obtained pretest results most of the knowledge of adolescent girls about anemia have less knowledge 10 people (50%), sufficient knowledge 6 people (30%), good knowledge 4 people (20%). And about the knowledge of adolescents after given education from the results of the post test most of the knowledge of adolescent girls about anemia has good knowledge 12 people (60%), sufficient knowledge 4 people (20%), less knowledge 4 people (20%). These results show an increase in knowledge of participants after providing this education and an increase in Hb levels after being given Fe teblet. It is expected that health facilities should be active in counseling and monitoring. Schools should support the habit of taking TTD, and adolescents are expected to increase awareness of healthy eating patterns and regular consumption of TTD. Abstrak Remaja putri merupakan kelompok yang rentan mengalami anemia akibat pertumbuhan yang pesat serta asupan zat gizi yang kurang seimbang. Anemia yang tidak ditangani dapat berdampak negatif pada kesehatan reproduksi dan menurunkan kualitas generasi mendatang. Rendahnya pengetahuan tentang gizi dan kurangnya konsumsi Tablet Tambah Darah (TTD) turut memperburuk kondisi dan remaja usia 12-17 tahun yang mengalami anemia ringan sebanyak 9 orang memiliki Hb <11 gr/dl. Metode pelaksanaan yang digunakan dalam pengabdian masyarakat ini adalah penyuluhan kesehatan yang diberikan pada 4 sasaran yakni ibu hamil, ibu nifas, balita dan remaja. Namun prioritas masalah di RT 5 Kelurahan Gedangank, yakni kurangnya pengetahuan tentang anemia pada remaja. Pengabdian masyarakat ini dilakukan di Desa Gedanganak Kecamatan Ungaran Timur, Kabupaten Semarang, pada remaja putri usia 13-17 tahun sejumlah 20 orang, tanggal 14 Juni 2025. Hasil pengabdian masyarakat didapatkan hasil pretest sebagian besar pengetahuan remaja putri tentang anemia memiliki pengetahuan kurang 10 orang (50%), pengetahuan cukup 6 orang (30%), pengetahuan baik 4 orang (20%). Dan tentang pengetahuan remaja setelah diberikan edukasi dari hasil post test sebagian besar pengetahuan remaja putri tentang anemia memiliki pengetahuan baik 12 orang (60%), pengetahuan cukup 4 orang (20%), pengetahuan kurang 4 orang (20%). Hasil ini menunjukkan peningkatan pengetahuan peserta setelah pemberian edukasi tersebut dan peningkatan kadar Hb setelah diberikan teblet Fe. Diharapkan fasilitas kesehatan diharapkan aktif dalam penyuluhan dan pemantauan. Sekolah sebaiknya mendukung kebiasaan minum TTD, dan remaja diharapkan meningkatkan kepedulian terhadap pola makan sehat dan konsumsi TTD secara teratur.